Príprava monoklonálnych protilátok proti povrchovým antigénom buniek hovädzieho dobytka - Dusinský, R; Simon, M; Nouzovská, D (Veterinarni medicina, 1988)
The BALB/c mice were immunized three times with bovine lymphocytes and thrombocytes in vivo. Besides, dissociated spleens of the mice were immunized with bovine lymphocytes in vitro. Hybridomas producing monoclonal antibodies were formed as a result of the fusion of the spleen cells with the murine myeloma cells. On the whole, four fusions were performed after immunization in vivo and three fusions after immunization in vitro, and 70 stable hybridoma clones were obtained. Five monoclonal antibodies exhibited an identical specific reaction only with bovine thrombocytes, two antibodies reacted only with a certain limited population of bovine spleen cells. The remaining monoclonal antibodies exhibited no tissue specificity and were bound to the lymphocytes of peripheral blood, lymph nodes, thymus, and spleen, to thrombocytes, liver cells, and spermatozoa, but never to erythrocytes. As for the amount of the obtained hybridomas and specific antibodies, no significant difference was observed in the effectiveness of in vivo and in vitro immunization.
Keywords: Mice; monoklonální protilátky; Methods; Antibodies, Monoclonal; Antigens, Surface; ELISA; Animals; antigeny povrchové; Cattle; myši inbrední BALB C; zvířata; metody; myši; Mice, Inbred BALB C; skot; Enzyme-Linked Immunosorbent Assay